Intellectual capital as a factor of innovative sustainable development - Bielienkova, O.Iu.; Loktionova, Ya.F.; Stetsenko, S.P.; Tуtok V.V. (Ways to Improve Construction Efficiency, 2022)
The article examines the genesis of the concept of "sustainable development" and its influence on the sustainable development of intellectual capital. It was determined that the development of intellectual capital contributes to the realization of all the Sustainable Development Goals (SDGs), providing the necessary knowledge, skills, innovations and opportunities to solve the world’s most pressing sustainable development problems. Intellectual capital is a valuable resource for promoting economic, social and environmental progress, comprehensively balanced development of society. Intellectual capital plays a key role in achieving both individual targets and the overall SDGs by 2030. The study of the impact of intellectual capital on the achievement of the Sustainable Development Goals is of great relevance and importance, as it provides valuable information on how human knowledge, skills and experience can be used to address complex, interconnected global challenges. Understanding this relationship allows us to develop more effective strategies and actions to promote sustainable development and create a better future for all. As a result of the analysis, it was found that the implementation of all seventeen Sustainable Development Goals depends on the influence of intellectual capital. At the same time, the so-called "spiral effect" arises, when the development of intellectual capital will contribute to the achievement of such goals as gender equality, decent work and economic growth, quality education, poverty alleviation, development of industry, innovation and infrastructure, reduction of inequality, sustainable development of cities and communities , in turn, the achievement of these goals will create favorable conditions for the growth of intellectual capital, becoming an impetus for its further development. Such an approach to the description of progressive growth not only corresponds to the principles of comprehensively balanced development, but will also allow creating a model of the influence of the components of intellectual capital on the development of an enterprise, industry, sector of the economy or the economic system as a whole..